Exploring Students’ Perceptions of African American Vernacular English (AAVE) in English Learning Contexts at University - Valen Alka Bilal Ananda; Wahyudin Wahyudin; Maghfira Maghfira; Mochtar Marhum (Journal of English Language and Education, 2026)
African American Vernacular English (AAVE) is a rule-governed variety of English that remains marginalized in many EFL classrooms, where Standard English dominates instruction. In Indonesia, students are increasingly exposed to AAVE through digital media, yet little is known about their perceptions of this variety. This study explored students’ perceptions of AAVE in English learning contexts at Tadulako University. A descriptive qualitative design was employed, with data collected through semi-structured interviews involving three eighth-semester English Education students. The data were analyzed using thematic analysis. The findings revealed three major themes: students’ initial impressions and emotional responses to AAVE, their views on its legitimacy and role in English education, and the influence of digital media on their perceptions and language use. Overall, the participants perceived AAVE as a legitimate and culturally meaningful variety of English while recognizing Standard English as more appropriate for formal academic settings. Although the findings provide in-depth insights into students’ perceptions, the small sample size limits the transferability of the results to broader EFL contexts. Nevertheless, this study highlights the importance of introducing diverse English varieties in EFL classrooms to promote linguistic awareness, cultural understanding, and inclusive language education.